Multi-stream part-fused graph convolutional networks for skeleton-based gait recognition - Likai Wang; Jinyan Chen; Zhenghang Chen; Yuxin Liu; Haolin Yang (Connection Science)
Gait recognition, a task of identifying people through their walking pattern, has attracted more and more researchers' attention. At present, most skeleton-based gait recognition approaches extract gait features from merely joint coordinates. However, the information, e.g. bone and motion, is equally instructive and discriminative for gait recognition. Thus, this paper proposes a novel multi-stream part-fused graph convolutional network, MS-Gait, to fuse part-level information and capture multi-order features from skeleton data. To be specific, we integrate a channel attention learning mechanism into the graph convolutional networks (GCN) to improve the representational power. In addition, part-level information is merged by capturing features from the skeleton graph and its subgraphs concurrently. Finally, a multi-stream strategy is proposed to model joint, bone, and motion dynamics simultaneously, which is proven to effectively improve the recognition accuracy. On the popular CASIA-B dataset, extensive experiments demonstrate that our method can achieve state-of-the-art performance and is robust to confounding variations.